Increased Resource Use in Lung Transplant Admissions in the Lung Allocation Score Era - Maxwell, Bryan G. (Am J Respir Crit Care Med, 2015)
Rationale: In 2005, the lung allocation score (LAS) was implemented to prioritize organ allocation to minimize waiting-list mortality and maximize 1-year survival. It resulted in transplantation of older and sicker patients without changing 1-year survival. Its effect on resource use is unknown. Objectives: To determine changes in resource use over time in lung transplant admissions. Methods: Solid organ transplant recipients were identified within the Nationwide Inpatient Sample (NIS) data from 2000 to 2011. Joinpoint regression methodology was performed to identify a time point of change in mean total hospital charges among lung transplant and other solid-organ transplant recipients. Two temporal lung transplant recipient cohorts identified by joinpoint regression were compared for baseline characteristics and resource use, including total charges for index hospitalization, charges per day, length of stay, discharge disposition, tracheostomy, and need for extracorporeal membrane oxygenation. Measurements and Main Results: A significant point of increased total hospital charges occurred for lung transplant recipients in 2005, corresponding to LAS implementation, which was not seen in other solid-organ transplant recipients. Total transplant hospital charges increased by 40% in the post-LAS cohort ($569,942 [$53,229] vs. $407,489 [$28,360]) along with an increased median length of stay, daily charges, and discharge disposition other than to home. Post-LAS recipients also had higher post-transplant use of extracorporeal membrane oxygenation (odds ratio, 2.35; 95% confidence interval, 1.56–3.55) and higher incidence of tracheostomy (odds ratio, 1.52; 95% confidence interval, 1.22–1.89). Conclusions: LAS implementation is associated with a significant increase in resource use during index hospitalization for lung transplant.